Let f (x) = –5x + 3 and g(x) = 6x – 2. Find f • g and its domain.

1 answer

To find f • g, we need to substitute g(x) into f(x). So we have:

f • g(x) = f(g(x)) = f(6x - 2)

Now, substitute f(x) into the expression above:

f(6x - 2) = -5(6x - 2) + 3 = -30x + 10 + 3 = -30x + 13

The domain of f • g is the same as the domain of g(x), which is all real numbers because there are no restrictions on x in the expression 6x - 2.

Therefore, the domain of f • g is (-∞, +∞).
Similar Questions
  1. The random variables X and Y have the joint PMFpX,Y(x,y)={c⋅(x+y)2,0,if x∈{1,2,4} and y∈{1,3},otherwise. All answers in
    1. answers icon 3 answers
  2. Using the expression 56xy + 5 -6x + y/20,find the following:a. Find two sums. b. find the terms of the expression. c. find a
    1. answers icon 1 answer
  3. Solve the following problems by using the binomial formula.a. If n = 4 and p = .10 , find P(x = 3) . b. If n = 7 and p = .80 ,
    1. answers icon 3 answers
  4. Given the function: f(x) = x^2 + 1 / x^2 - 9a)find y and x intercepts b) find the first derivative c) find any critical values
    1. answers icon 0 answers
more similar questions